Acclimation of Nodularia spumigena CCY9414 to inorganic phosphate limitation – Identification of the P-limitation stimulon via RNA-seq - Santoro, Mariano; Hassenrück, Christiane; Labrenz, Matthias; Hagemann, Martin (Frontiers in Microbiology, 2023)
Nodularia spumigena is a toxic, filamentous cyanobacterium capable of fixing atmospheric N2, which is often dominating cyanobacterial bloom events in the Baltic Sea and other brackish water systems worldwide. Increasing phosphate limitation has been considered as one environmental factor promoting cyanobacterial mass developments. In the present study, we analyzed the response of N. spumigena strain CCY9414 towards strong phosphate limitation. Growth of the strain was diminished under P-deplete conditions; however, filaments contained more polyphosphate under P-deplete compared to P-replete conditions. Using RNA-seq, gene expression was compared in N. spumigena CCY9414 after 7 and 14 days in P-deplete and P-replete conditions, respectively. After 7 days, 112 genes were significantly up-regulated in P-deplete filaments, among them was a high proportion of genes encoding proteins related to P-homeostasis such as transport systems for different P species. Many of these genes became also up-regulated after 14 days compared to 7 days in filaments grown under P-replete conditions, which was consistent with the almost complete consumption of dissolved P in these cultures after 14 days. In addition to genes directly related to P starvation, genes encoding proteins for bioactive compound synthesis, gas vesicles formation, or sugar catabolism were stimulated under P-deplete conditions. Collectively, our data describe an experimentally validated P-stimulon in N. spumigena CCY9414 and provide the indication that severe P limitation could indeed support bloom formation by this filamentous strain.